G-quadruplex ligands:potent inhibitors of telomerase activity and cell proliferation in plasmodium falciparum (2020)
Telomeres are DNA and protein structures located at the ends of eukaryotic chromosomes. These structures maintain chromosomal stability by impeding chromosomal ends from being recognized and processed as fragmented DNA. They also support the complete replication of the genome by providing mechanisms that solve the end-replication problem. Telomeric DNA is formed of short, repeating, guanine-rich sequences. The G-rich sequence extends towards the 3′ end, forming a protruding single-stranded end that can acquire a conformation known as G-quadruplex. The ligands stabilizing this structure are potent inhibitors of telomerase activity, a catalytic activity necessary to compensate for the loss of telomeric DNA that occurs in each round of replication. In the absence of telomerase, telomeres shorten after a given number of cell divisions, after which the cell enters a senescence state and finally dies. In the presence of telomerase activity, telomeres are preserved, and cells reach a state of indefinite replication or immortalization. This study analyzed the effect of two ligands of the G-quadruplex (TMPyP4 and Telomestatin) on the telomerase activity and cell proliferation of Plasmodium falciparum, given that this parasite has a high proliferation rate and an almost indefinite replication capacity. The effect of the ligands on telomerase activity was evaluated using the TRAP (Telomere Repeat Amplification Protocol) activity assay, which was performed in the presence of increasing concentrations of each ligand. In this study, TMPyP4 showed the highest inhibitory effect, reaching 50% inhibition at a 5 μM concentration. Regarding proliferation, both ligands drastically affected parasite growth, but Telomestatin had a stronger effect. After three days of treatment, parasite growth decreased by 90%. Thus, it is possible that this compound interferes with other vital pathways for the parasite beyond the elongation of telomeric DNA by telomerase.